THE DEVELOPMENT OF BUKHARA AS A CITY - Hashimova S.A.; Butayev B.B.; Usmonov G'.X. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article tells about the ancient city of Bukhzrai and its development as a city. Bukhara was a famous trading city on the Great Silk Road. Its center is a treasury of historical and architectural monuments of the Middle Ages, which are under the protection of the state.